Aplikasi Terapi Bercakap - Cakap Pada Tn. N dengan Gangguan Persepsi Sensori: Halusinasi Pendengaran di Jampang Kulon - Siti Patimah (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Problemsof mental health nursing that may arise in response to mental disorders experienced by an individual include the risk of violent behavior, self-care deficits, social isolation and impaired sensory perception: hallucinations. The hallucinations themselves consist of auditory hallucinations, visual hallucinations, tactile hallucinations, tasting hallucinations, and olfactory hallucinations. Auditory hallucination is a stimulus or stimulus disorder in which the client hears voices that do not exist, especially human voices, usually the client hears the voices of people according to what the client thinks which then orders the client to do something that can sometimes harm oneself, others, and the environment. In the assessment stage, data were obtained showing the client experiencing sensory perception disorders: auditory hallucinations, which were obtained from the precipitation factor. The client often heard voices without any form when the client was alone. Mr. N has 4 nursing problems including sensory perception disorders: auditory hallucinations, risk of violent behavior, social isolation and low self-esteem, but the author focuses on one diagnosis, namely the problem of hallucinations. The action taken is to practice conversational therapy with other people to reduce the patient's level of hallucinations. The conclusion of the given action has been reached where the client is able to converse with other people when the client experiences hallucinations.